Web‐above‐a‐Ring (WAR) and Web‐above‐a‐Lens (WAL): Nanostructures for Highly Engineered Plasmonic‐Field Tuning and SERS Enhancement. Issue 31 (23rd June 2021) - Lee, Soohyun; Lee, Sungwoo; Son, Jiwoong; Kim, Jae‐Myoung; Lee, Junghwa; Yoo, Sungjae; Haddadnezhad, MohammadNavid; Shin, Jieun; Kim, Jeongwon; Nam, Jwa‐Min; Park, Sungho
Abstract: Synthetic strategies of web‐above‐a‐ring (WAR) and web‐above‐a‐lens (WAL) nanostructures are reported. The WAR has a controllable gap between the nanoring core and a nanoweb with nanopores for the effective confinement of electromagnetic field in the nanogap and subsequent surface‐enhanced Raman scattering (SERS) of Raman dyes inside the gap with high signal reproducibility, which are attributed to the generation of circular 3D hot zones along the rim of Pt@Au nanorings with wrapping nanoweb architecture. More specifically, Pt@Au nanorings are adopted as a plasmonic core for structural rigidity and built porous nanowebs above them through a controlled combination of galvanic exchange and the Kirkendall effect. Both nanoweb and nanolens structures are also formed on Pt@Au nanoring, which is WAL. structure. Remarkably, plasmonic hot zone, nanopores, and hot lens are formed inside a single WAL nanostructure, and these structural components are orchestrated to generate stronger SERS signals. Abstract : Web‐above‐a‐rings (WAR) with controllable intra‐gap distance are step‐wise synthesized. This approach allows to make single‐particle SERS inactive Pt@Au nanorings into SERS active with high reproducibility and long‐term stability. The existence of nanowebs enhances near electromagnetic field with dependence of intra‐gap distance. Additionally, the hybridization feature between the core nanoring and the porous nanoweb is observed.